Identification and analysis of functional regulatory elements and RNAi silencing genes in mandarin clementine (Citrus clementina) - Maryam Noor; Iqra Mehar; Hadia Hussain; Abdel-Rhman Z. Gaafar; Mutwakel Dabiellil; Tawaf Ali Shah (Journal of Plant Interactions)
This study aimed to identify the RNA interference-associated AGO, DCL, and RDR gene families in Citrus clementina using various bioinformatics approaches. To our knowledge, there has not yet been a genome-wide investigation into the AGO, DCL, and RDR gene families in Citrus clementina, even though these families have been recognized in other species. The investigation identified 12 CcAGOs, 5 CcDCLs, and 1 CcRDR gene within the Citrus clementina genome, corresponding to the RNAi genes found in the model organism Arabidopsis thaliana. The results showed significant homogeneity within the same gene family, with the majority of RNAi genes localized in the nucleus. Furthermore, the study revealed that 18 of the identified RNAi genes were significantly involved in RNA gene silencing processes. These findings provide valuable insights for the molecular exploration of RNAi genes, potentially aiding in the improvement of Citrus clementina crops in response to stress factors.